2007
DOI: 10.1007/s00038-007-6116-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Epidemiology after the German Reunification: East vs. West or Poor vs. Rich?

Abstract: Small-area analyses are required to disentangle the association between socio-economic inequalities and health in Germany. In such analyses, not only individual but also contextual (e.g. area level) characteristics need to be included. Contextual variables can be used to group smaller areas such as counties into clusters with similar properties. Thus, individual survey data can be linked with contextual characteristics while maintaining data protection and at the same time achieving sufficiently large case num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 9 publications
0
30
2
11
Order By: Relevance
“…Innerhalb der alten Bundesl ä nder l ä sst sich eine Zunahme regionaler Unterschiede bei der Arbeitslosenquote, Ä rztedichte und dem Frauenanteil feststellen. Dieser Befund spricht daf ü r, dass der sozialepidemiologische Erkenntnisgewinn eines Ost-WestVergleich dahingehend weiter abgenommen hat, dass es sich um einen Vergleich in sich sehr heterogener, zum Teil heterogener gewordener Entit ä ten handelt [8] . Die Entwicklung regionaler Unterschiede zwischen den Jahren 1995 und 2005 bzw.…”
Section: Statistische Methoden Der Datenauswertungunclassified
See 1 more Smart Citation
“…Innerhalb der alten Bundesl ä nder l ä sst sich eine Zunahme regionaler Unterschiede bei der Arbeitslosenquote, Ä rztedichte und dem Frauenanteil feststellen. Dieser Befund spricht daf ü r, dass der sozialepidemiologische Erkenntnisgewinn eines Ost-WestVergleich dahingehend weiter abgenommen hat, dass es sich um einen Vergleich in sich sehr heterogener, zum Teil heterogener gewordener Entit ä ten handelt [8] . Die Entwicklung regionaler Unterschiede zwischen den Jahren 1995 und 2005 bzw.…”
Section: Statistische Methoden Der Datenauswertungunclassified
“…Hinsichtlich der regionalen Erwerbsm ö glichkeiten z ä hlen dazu Expositionen wie Lohniveau, Qualit ä t der Arbeitsbedingungen, Sicherheit der berufl ichen Perspektive und die damit verbundene Neigung, Krankheiten zu verschleppen [13] . Die regionale Infrastrukturausstattung und damit auch die Erreichbarkeit der sozial und gesundheitlich bedeutsamen Versorgungseinrichtungen d ü rfte der zweite gro ß e Bereich sein, aus dem sich gesundheitsrelevante Expositionen ergeben [8] . Die angef ü hrten Untersuchungen belegen zwar ausgepr ä gte regionale Unterschiede in den Lebensverh ä ltnissen und damit assoziierte gesundheitliche Unterschiede.…”
unclassified
“…Individual risk factors such as smoking or a low socio-economic status and their effect on health have been examined in considerable detail, and explanatory models describing pathways and associations have been proposed. Our own previous work has shown that existing explanatory models often fail to acknowledge the role of ''space'', by which we mean contextual variables located at the level of regions, counties and neighbourhoods, as compared to factors at individual level (Razum et al 2008). In addition, they put very little emphasis on ''time'', i.e., the temporal dimension of the association of contextual factors and health (Voigtländer et al 2012(Voigtländer et al , 2014Richter and Blane 2013).…”
Section: The Role Of Individual and Contextual Factorsmentioning
confidence: 99%
“…Differences are likely to exist compared with privately insured persons (< 10 %), although offers of cancer screening tests would be similar [46,47]. General health disparities may exist on the city and county level rather than between federal states or east and west Germany [48]. In one recent survey, the estimate of lifetime colonoscopy use in the federal state of Hesse was very close to the average of the state-specific estimates [13].…”
mentioning
confidence: 99%